Relationship Knowledge about Covid-19 with Hand Washing Habits in Indrasari Village Martapura District Banjar Regency South Kalimantan Province in 2021 - Annalia Wardhani; Melinda Restu Pertiwi (D'Nursing and Health Journal (DNHJ), 2021)
Introduction: The spread of Covid-19 can be prevented by various efforts. The one management that must be applied by all communities in various settings is diligently washing hands using soap in running water. The purpose of this study was to determine the relationship between public knowledge about Covid-19 and hand washing habits in Indrasari Village, Martapura District, Banjar Regency, South Kalimantan Province in 2021. Method: The research design used in this study was descriptive analytic with a correlational study and a cross sectional approach with the research population. as many as 6,567 people. The sampling technique used is Accidental Sampling with a total sample of 377 respondents. Result: The results of the research conducted through the spearman rank test showed a value of = 0.000 p <α (0.05) which indicates that there is a relationship between public knowledge about Covid-19 and hand washing habits. It is hoped that health workers will continue to carry out continuous counseling about the importance of implementing good and correct hand washing habits. Conclusion: There is a relationship between public knowledge about Covid-19 and the habit of washing hands in Indrasari village, Martapura district, Banjar district, South Kalimantan province in 2021.